2023
DOI: 10.12911/22998993/166557
|View full text |Cite
|
Sign up to set email alerts
|

Content of Heavy Metals in Various Biochar and Assessment Environmental Risk

Abstract: Biochar is a product of biomass pyrolysis and has a number of environmentally beneficial uses, but it can also pose risks if not managed properly. These risks are mainly due to the chemical structure of biochar, the content of heavy metals. The aim of this study was to evaluate the mobility and environmental risk of heavy metals in biochar produced from plant biomass (BB), municipal solid waste (MSW), compost (C) and coal refuse (CR). Pollution indices were calculated: geo-accumulation index (GAI), ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Although this comparison should be intended as a first attempt, it allows for the identification of environmental categories likely affected by the change in composition, emphasizing the need for particular attention to categories addressing toxicity (i.e., FETP, METP, HTPc, and HTPnc). In general, there is considerable debate regarding the potential contamination of biochar with leachable metals, which adversely affect the toxicity parameters in LCA [79]. The presence of metals is closely linked to the feedstock from which the biochar is derived.…”
Section: Discussionmentioning
confidence: 99%
“…Although this comparison should be intended as a first attempt, it allows for the identification of environmental categories likely affected by the change in composition, emphasizing the need for particular attention to categories addressing toxicity (i.e., FETP, METP, HTPc, and HTPnc). In general, there is considerable debate regarding the potential contamination of biochar with leachable metals, which adversely affect the toxicity parameters in LCA [79]. The presence of metals is closely linked to the feedstock from which the biochar is derived.…”
Section: Discussionmentioning
confidence: 99%
“…However, these heavy metals did not exceed the guidelines set by the IBI. It was also found that biochar derived from plant biomass held the lowest concentrations of heavy metals, while coal-refuse biochar displayed the highest concentrations (Kujawska, 2023). For example, the recorded concentrations of cadmium, chromium, copper, nickel, lead, and zinc in plant biomass were 0.03, 10.3, 19.7, 10.5, 10.9, and 55.5 mg kg -1 , respectively, while those in coalrefuse biochar were 0.25, 16.9, 34.1, 14.3, 15.1, and 71.3 mg kg -1 , respectively (Kujawska, 2023).…”
Section: Potential Source Of Toxicantsmentioning
confidence: 96%
“…For example, biochar made from biomass high in VOCs, such as manure or food waste, is more likely to have a higher VOC content compared with biochar made from biomass that is low in VOCs, such as wood (Saletnik et al, 2019). Likewise, biochar produced from various sources, including plant biomass, municipal solid waste, compost, and coal refuse exhibited a range of concentrations for chromium (5.88-69.4), nickel (4.60-33.4), copper (3.96-40.3), zinc (9.61-138), lead (1.71-36), cadmium (0.12-0.17), and arsenic (0.12-1.53) mg kg -1 (Kujawska, 2023). However, these heavy metals did not exceed the guidelines set by the IBI.…”
Section: Potential Source Of Toxicantsmentioning
confidence: 99%
“…The increase in fixed carbon and ash content with temperature can be caused by the removal of volatile matter, leaving the more stable carbon and ash-forming inorganic matter in biomass [55]. During pyrolysis, heavy metals, like chromium (Cr), nickel (Ni), copper (Cu), zinc (Zn), arsenic (As), cadmium (Cm), and lead (Pb), accumulate in the ash fractions [56]. This is important, since the ash content present in soil has a significant impact on the growth of plants.…”
Section: Biochar's Fuel Propertiesmentioning
confidence: 99%